Analisis Pengaruh Literasi Keuangan Syariah, Financial Self Efficacy dan Fintech Payment terhadap Manajemen Keuangan Pribadi Mahasiswa: Studi Kasus Mahasiswa FEBI UIN STS Jambi - Putri Handayani Lestari; Titin Agustin Nengsih; Fitri Ana Siregar (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
Students are equipped with the knowledge necessary to acquire the skills they will obtain after completing their education through the use of various facilities, learning resources and learning methods that are in line with their abilities, and are expected to be able and willing to face life. With basic knowledge and comprehensive financial insight, students are expected to be able to manage their finances appropriately and wisely and determine policies to prevent financial problems. It is believed that students' personal financial management can be influenced by financial literacy, financial self-efficacy, and fintech payments. The aim of this research is to determine the influence of financial literacy, financial self-efficacy, and fintech payments on students' personal financial management among FEBI UIN STS Jambi students. This research was carried out using a quantitative descriptive approach and carried out direct observations in the field. The research results obtained are that there is a positive and significant influence of the variables financial literacy (X1), financial self-efficacy (X2), and fintech payments (X3) on students' personal financial management (Y). And the influence of the variables sharia financial literacy, financial cell efficacy and fintech payments on students' personal financial management has an influence of 71.9% and the rest is influenced by other variables from outside this research.